Variational quantum eigensolver for approximate diagonalization of downfolded Hamiltonians using generalized unitary coupled cluster ansatz. (16th June 2021) - Nicholas P, Bauman; Chládek, Jaroslav; Veis, Libor; Pittner, Jiří; Karol, Kowalski
Abstract: In this paper, we discuss the utilization of variational quantum solver (VQE) and recently introduced generalized unitary coupled cluster (GUCC) formalism for the diagonalization of downfolded/effective Hamiltonians in active spaces. In addition to effective Hamiltonians defined by the downfolding of a subset of virtual orbitals we also consider their form defined by freezing core orbitals, which enables us to deal with larger systems. We also consider various solvers to identify solutions of the GUCC equations. We use N2, H2 O, and C2 H4, as benchmark systems to illustrate the performance of the combined framework.